Pediatric sweet syndrome. Issue 10 (19th October 2021) - Zhou, Albert E.; Weddington, Charles Maxwell; Ge, Shealinna; Hoegler, Karl M.; Driscoll, Marcia S.
Abstract: Pediatric Sweet syndrome is a rare dermatosis often triggered by a prodromal illness or infection and characterized histologically by a dense neutrophilic infiltrate. We report a 2‐year‐old girl with a classic presentation of Sweet syndrome following an acute thumb paronychia, who had a negative history of malignancy or immunodeficiency. Abstract : Pediatric Sweet syndrome is a rare dermatosis often triggered by a prodromal illness or infection and characterized histologically by a dense neutrophilic infiltrate. We report a 2‐year‐old girl with a classic presentation of Sweet syndrome following an acute thumb paronychia, who had a negative history of malignancy or immunodeficiency.